VAKSIN INAKTIF Klebsiella pneumoniae DENGAN PERLAKUAN SINAR GAMMA DAN PEMANASAN SUHU 65° C - I. Djajanegara; I. Sugoro (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Klebsiella pneumoniae is one of coliform bacteria which cause human dan mammalian diseases. The bacteria dominate in dairy cow milk which has suffered from mastitis and has resistent on antibiotic. Vaccination is one of aims to prevent the diseases. Nuclear technique could be used to have a vaccine candidate. This research was conducted to get the influence of inactivated K. pneumoniae by gamma irradiated and heat inactivated as vaccine candidate on mice. The treatment were positive control (infected by K. pneumoniae), Negative control (injection by physiologies NaCl solution), 800 Gy (infected by K. pneumoniae has inactivated with 800 Gy), 1000 Gy (infected by K. pneumoniae has inactivated with 1000 Gy), 30’ (infected by K. pneumonia has inactivated with heat 65° C for 30’), and 45’ (infected by K. pneumoniae has inactivated with heat 65° C for 30’). The parameters were physical condition, weight, organ, total number of red, white blood cells, and intraperitoneal macrophage. The results showed that irradiated vaccines were better than heat. % mortality of positive control was 100% but the treatments were 0%. The physic condition of mice was normal for irradiated treatment, but not for negative control and heat treatment. The weight gain of mice after vaccination and challenge test were decreased and back normal after 2 days. The organ condition of mice was normal after vaccination and challenge test. The total number of red and white blood cells showed the same pattern for all treatment after vaccination and challenge test, but the total of intraperitoneal macrophage was increased after 4 hours vaccination. Based on the results showed that irradiated vaccine has potential to develop as vaccine candidate.